Long event-free survival after anti-BCMA CAR-T cell treatment for relapsed and refractory multiple myeloma patients: Two case reports. Issue 18 (7th May 2021) - Xu, Jinhuan; Ming, Xi; Wang, Chunyan; Xu, Bi; Xiao, Yi
Abstract: Introduction: Chimeric antigen receptor T (CAR-T) cells targeting B-cell maturation antigen (BCMA) have been used in the treatment of relapsed and refractory multiple myeloma (RRMM). The response rate and the depth of responses induced by anti-BCMA CAR-T cells are impressive. However, despite this, remissions are not sustained, and the majority of patients eventually relapse. Patient concerns: Two patients with multiple myeloma (MM) were selected to enroll in a phase I study involving anti-BCMA CAR-T cells (ChiCTR-OPC-16009113) because they did not have the good effect after traditional treatment. One is a 48-year-old male patient who received a diagnosis of IgG lambda MM in June 2015, he has received 4 cycles of cyclophosphamide, bortezomib, and dexamethasone (CyBorD) and obtained a complete response (CR). Approximately 11 months later, the disease progressed. Subsequent treatment included regimens incorporating liposomal doxorubicin, bortezomib, and dexamethasone (3 cycles); the response was poor, and the disease kept progressing. Another 65-year-old female patient received a diagnosis of IgG lambda MM in September 2016, she has received induction therapy with 1 cycle of bortezomib and dexamethasone (VD) and 4 cycles of lenalidomide and dexamethasone, the response was poor. Diagnosis: Both patients were diagnosed with RRMM according to the International Myeloma Working Group criteria. Interventions: Both patients received infusions of anti-BCMA CAR-T cells following an induction chemotherapy regimen of cyclophosphamide and fludarabine. Outcomes: Both of them achieved a stringent CR at the 30th day with minimal residual disease-negative bone marrow by flow cytometry and serum monoclonal protein was undetectable at 4 and 10 months after cell transfusion. The CR has persisted in the 2 patients for >36 months. Conclusions: Our findings demonstrate the anti-BCMA CAR-T cell treatment is a feasible therapeutic option for patients with RRMM. Fewer early lines of treatment may be beneficial to maintain the efficacy of CAR-T cells. Trial registration: ChiCTR-OPC-16009113. Abstract : Supplemental Digital Content is available in the text